Utility of CB-NAAT in cutaneous tuberculosis: A prospective observational study - Parul Verma; Srishti Tripathi; Swastika Suvirya; Prakriti Shukla; Amita Jain; Atin Singhai; Urmila Singh; Nishant Verma (Clinical Epidemiology and Global Health)
Problem considered: Conventional diagnostic techniques for diagnosing Cutaneous tuberculosis (CTB) have variable sensitivity, specificity and are time-consuming. CB-NAAT is based on real-time PCR and can be helpful in rapid detection of mycobacterial antigens along with the detection of rifampicin resistance. Our study aims at detecting the efficacy of CB-NAAT in the diagnosis of CTB as compared to conventional diagnostic techniques like histopathology and culture. Methods: Skin biopsies were taken from the representative lesions in 41 patients of CTB. One sample was sent for histopathology whereas the other sample was sent for CB-NAAT, liquid culture -DST (drug sensitivity testing) and smear microscopy. Results: Out of 41 patients with cutaneous TB, CB-NAAT was positive in 6 (14.63 %), culture was positive in 8 (19.5 %) and histopathology was compatible in 26 (63.4 %) patients. CB-NAAT was positive in 3 out of 8 culture positive cases and 4 out of 26 histopathology compatible cases. The sensitivity and specificity of gene Xpert MTB/RIF in detecting TB when compared to culture were 37.5 % and 91 % respectively and Positive- and Negative-predictive values were 50 % and 85.7 % respectively. Xpert MTB/RIF could identify an additional 3 cases, where all other microbiological investigations were negative. Out of 6 cases that were CB-NAAT positive, 3 showed Rifampicin resistance. Conclusions: The CB-NAAT test has variable diagnostic accuracy in the diagnosis of CTB which can vary with the clinical specimen. It can prove as a promising tool for early detection of cutaneous TB along with drug-resistant TB especially in the high endemic zones.